A solvent-free polyurethane modified acrylate adhesive and preparation method thereof

By using monomers such as methyl acrylate, butyl acrylate and hydroxyethyl acrylate in solvent-free adhesives, a polyurethane modified acrylate adhesive with high viscosity and strong peeling properties is formed, which solves the problems of low viscosity and insufficient peeling strength of the existing adhesives, meets the needs of the food packaging industry and achieves safe and environmentally friendly production.

CN115851206BActive Publication Date: 2025-05-02GUANGDONG EMEIDA CHEMICAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211504891.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-29
Publication Date
2025-05-02
Estimated Expiration
2042-11-29

AI Technical Summary

Technical Problem

The existing solvent-free adhesives have shortcomings in terms of viscosity and peel strength, which is difficult to meet the demand for high viscosity and strong peeling properties of the food packaging industry.

Method used

Methyl acrylate is used as the hard monomer, butyl acrylate and hydroxyethyl acrylate are used as the soft monomer, azobisisobutyronitrile is used as the initiator, and polyether glycol is used as the blending component. Through the compounding reaction of component A and component B, a high viscosity solvent-free polyurethane modified acrylate adhesive is formed.

Benefits of technology

It significantly improves the viscosity and peel strength of the adhesive, and can more effectively bond and peel off food packaging substrates to meet the needs of the food packaging industry. At the same time, due to the absence of solvents, the product is safe, non-toxic, environmentally friendly and has low production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115851206B_ABST
    Figure CN115851206B_ABST
Patent Text Reader

Abstract

The invention discloses a solvent-free polyurethane modified acrylate adhesive and a preparation method thereof, and belongs to the technical field of adhesives. The adhesive is composed of component A and component B stored independently of each other; wherein component A is composed of the following components by mass: 38-42 parts of polyether glycol, 18-22 parts of methyl methacrylate, 28-32 parts of butyl acrylate, 8-12 parts of hydroxyethyl acrylate, 0.1-0.5 parts of azobisisobutyronitrile; component B is composed of the following components by mass: 39-43 parts of polyether glycol, 58-62 parts of isophorone diisocyanate, 0.1-0.5 parts of dibutyltin dilaurate; when the adhesive is used, component A and component B are compounded and reacted according to the volume ratio of component A: component B = 25%-85%: 15%-75%. The adhesive prepared by the present invention can effectively improve viscosity and peel strength, and has a wide range of applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, and in particular to a solvent-free polyurethane modified acrylate adhesive and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of the e-commerce industry and the live streaming industry, the sales of packaged foods such as snacks have increased year by year, which has also led to a surge in demand in the food packaging market. Composite food packaging substrates generally include paper / paper composites, paper / aluminum composites, aluminum / plastic composites, and plastic / plastic composites. These food packaging substrates are usually bonded and composited with adhesives. Adhesives used in food packaging are required to be low-toxic or non-toxic, have high adhesion, low cost, easy to use, and green and environmentally friendly to meet the needs of the food packaging market.

[0003] There are many types of adhesives, most of which are water-based adhesives and solvent-based adhesives on the market. Among them, water-based adhesives have no volatile solvents and are environmentally friendly, but the viscosity and peel strength of the adhesive are not high, and they are only suitable for light packaging. Solvent-based adhesives have good water resistance and high viscosity, but the organic solvents such as benzene and ester solvents used in solvent-based adhesives are easy to evaporate and seep out, and long-term contact has certain toxic effects. In addition, both water-based and solvent-based adhesives need to be dried during the production process, which has high requirements for equipment technology and high production costs. Therefore, solvent-free adhesives can better meet the needs of the modern packaging market with their green and environmentally friendly, safe and non-toxic, low cost, and easy use. Solvent-free two-component adhesives refer to systems that do not contain any organic solvents, have a curing agent content of 100%, and are mainly composed of component A polyols or acrylates with -OH groups, component B polyurethane PU prepolymers with synthetic end groups of -NCO groups, and additives. When component A and component B are compounded and mixed, the -OH groups of polyols and acrylates will crosslink with the -NCO groups of polyurethane PU prepolymers, and the two substrates will be bonded after crosslinking and curing. However, the existing solvent-free adhesives on the market still have the problems of low viscosity and low peel strength. Therefore, it is very necessary to develop a solvent-free polyurethane modified acrylate adhesive with high viscosity and good peel strength that can be used in the food packaging industry. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the object of the present invention is to provide a solvent-free polyurethane modified acrylate adhesive, which has high viscosity and can effectively improve the peel strength of the substrate.

[0005] To solve the above problems, the technical solution adopted by the present invention is as follows:

[0006] A solvent-free polyurethane modified acrylate adhesive, the adhesive is composed of component A and component B stored independently of each other; wherein:

[0007] Component A is composed of the following components in parts by mass: 38-42 parts of polyether diol, 18-22 parts of methyl methacrylate, 28-32 parts of butyl acrylate, 8-12 parts of hydroxyethyl acrylate, and 0.1-0.5 parts of azobisisobutyronitrile;

[0008] Component B is composed of the following components in parts by mass: 39-43 parts of polyether diol, 58-62 parts of isophorone diisocyanate, and 0.1-0.5 parts of dibutyltin dilaurate;

[0009] When the adhesive is used, component A and component B are compounded and reacted according to a volume ratio of component A: component B = 25%-85%: 15%-75%.

[0010] In the above formula, methyl methacrylate (MMA) in component A is a hard monomer used to provide the main hardness; butyl acrylate (BA) and hydroxyethyl acrylate (2-HEA) are soft monomers used to adjust the hardness and softness; polyether diol is used to provide OH groups to react with NCO groups; azobisisobutyronitrile (AIBN) is an initiator used to initiate the polymerization of the above acrylic monomers. In component B, polyether diol (PPG) is used to react with NCO groups to polymerize into chain segments, isophorone diisocyanate (IPDI) is used to react with OH groups to polymerize into chain segments, and dibutyltin dilaurate (DBTDL) is used as a catalyst to promote the reaction polymerization.

[0011] As a preferred embodiment of the present invention, the molecular weight of the polyether diol in component A is 300-800.

[0012] As a preferred embodiment of the present invention, the molecular weight of the polyether diol in component B is 1000-3000.

[0013] The present invention also provides a method for preparing the solvent-free polyurethane modified acrylate adhesive as described above, which comprises the following steps:

[0014] S1. Preparation of component A: Take polyether diol and heat it to 80-100° C. in a water bath; Take methyl methacrylate, butyl acrylate and hydroxyethyl acrylate and mix them, add part of azobisisobutyronitrile, stir and dissolve, and obtain a mixed solution of acrylate monomer containing azobisisobutyronitrile; slowly drop the mixed solution into the polyether diol and stir, keep the temperature for 0.5-1h after the dropwise addition is completed, then add the remaining azobisisobutyronitrile, react at 80-100° C. for 1-2h, cool to room temperature after the reaction is completed, and seal and store;

[0015] S2, preparation of component B: add isophorone diisocyanate to polyether diol, stir and slowly heat to 40-60°C, stop heating, allow to self-exotherm to 70-80°C, maintain this temperature and continue to react for 2-3h, add 0.1-0.5 parts of butyl tin dilaurate and continue to react for 2-3h, cool to room temperature after the reaction is completed, and seal and store;

[0016] S3. When in use, component A and component B are compounded and reacted according to a volume ratio of component A: component B = 25%-85%: 15%-75% to obtain the adhesive.

[0017] As a preferred embodiment of the present invention, the stirring speed when azobisisobutyronitrile is added dropwise in step S1 is 200-300 r / min.

[0018] As a preferred embodiment of the present invention, the stirring speed in step S2 is 250-350 r / min.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] The present invention uses methyl acrylate as a hard monomer, butyl acrylate and hydroxyethyl acrylate as soft monomers, azobisisobutyronitrile as an initiator, and polyether diol as a blending component to synthesize a high-viscosity component A acrylic ester polyol copolymer; polyether diol is reacted with isophorone diisocyanate, and dibutyltin dilaurate is used as a catalyst to synthesize a component B polyurethane PU prepolymer with an NCO group as an end group; and then the A and B components are polymerized according to a certain volume ratio to form a solvent-free polyurethane modified acrylic adhesive, which can effectively increase the viscosity of the adhesive and greatly improve the peel strength of the packaging material. The adhesive of the present invention does not use any solvent in the production process, is safe, non-toxic, environmentally friendly, and does not require a drying device, so the drying cost in production can be greatly reduced; component A and component B are produced separately and sealed for storage, which is convenient for storage and transportation. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a product photo of component A prepared in Example 1 of the present invention;

[0022] Figure 2 This is a temperature-viscosity curve of component A obtained in Example 1 of the present invention;

[0023] Figure 3 This is a product photo of component B prepared in Example 1 of the present invention;

[0024] Figure 4 This is a product photo of the adhesive prepared according to Example 1 of the present invention with component A at a volume ratio of 40%;

[0025] Figure 5FTIR spectra of component A, component B, and an adhesive prepared at a volume ratio of 40% of component A in Example 1 of the present invention;

[0026] Figure 6 This is a product photo of component B prepared in Comparative Example 1 of the present invention;

[0027] Figure 7 This is a product photo of the adhesive prepared according to Comparative Example 1 of the present invention with component A at a volume ratio of 40%;

[0028] Figure 8 This is a product photo of component B prepared in Comparative Example 2 of the present invention;

[0029] Fig. 9 This is a product photo of the adhesive prepared in Comparative Example 2 of the present invention with component A at a volume ratio of 40%;

[0030] Fig.10 The temperature-viscosity curve of component B prepared in Example 1 and Comparative Examples 1-2 of the present invention;

[0031] Fig.11 The temperature-viscosity curve of the adhesive obtained by mixing component A prepared in comparative example 1 of the present invention with component B at volume ratios of 85%, 70%, 55%, 40% and 25% respectively;

[0032] Fig.12 The temperature-viscosity curve of the adhesive obtained by mixing component A prepared in Example 1 of the present invention with component B at volume ratios of 85%, 70%, 55%, 40% and 25% respectively;

[0033] Fig.13 The temperature-viscosity curve of the adhesive obtained by mixing component A prepared in comparative example 2 of the present invention with component B at volume ratios of 85%, 70%, 55%, 40% and 25% respectively;

[0034] Fig.14 The following is a comparison chart of the peel strength of adhesives prepared at different mixing volume ratios on paper / aluminum foil of Comparative Example 1, Example 1 and Comparative Example 2 of the present invention;

[0035] Fig.15 The following is a comparison chart of the peel strength of adhesives prepared at different mixing volume ratios of Comparative Example 1, Example 1 and Comparative Example 2 of the present invention on paper / paper;

[0036] Fig.16 This is a comparison chart of the peel strength of adhesives prepared at different mixing volume ratios on paper / PE film of Comparative Example 1, Example 1 and Comparative Example 2 of the present invention;

[0037] Fig.17The following is a comparison chart of the peel strength of adhesives prepared at different mixing volume ratios on aluminum foil / PE film of Comparative Example 1, Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.

[0039] A method for preparing a solvent-free polyurethane modified acrylate adhesive comprises the following steps:

[0040] S1. Preparation of component A: Take polyether diol and heat it to 80-100° C. in a water bath; Take methyl methacrylate, butyl acrylate and hydroxyethyl acrylate and mix them, add part of azobisisobutyronitrile, stir and dissolve, and obtain a mixed solution of acrylate monomer containing azobisisobutyronitrile; slowly add the mixed solution dropwise to the polyether diol with a separatory funnel and stir, keep warm for 0.5-1h after the addition is completed, add the remaining azobisisobutyronitrile to a volumetric flask at once, react at 80-100° C. for 1-2h, cool to room temperature after the reaction is completed, and seal and store;

[0041] S2, preparation of component B: add isophorone diisocyanate to polyether diol, stir and slowly heat to 40-60°C, then stop heating, allow to self-exotherm to 70-80°C, maintain this temperature and continue to react for 2-3h, add 0.1-0.5 parts of butyl tin dilaurate and continue to react for 2-3h, cool to room temperature after the reaction is completed, and seal and store;

[0042] The reaction formula is as follows:

[0043]

[0044] S3. When in use, component A and component B are compounded and reacted according to a volume ratio of component A: component B = 25%~85%: 15%~75% to obtain the adhesive copolymer.

[0045] The main instruments used in the following examples and comparative examples are shown in Table 1.

[0046] Table 1 Names and manufacturers of main experimental instruments

[0047]

[0048] The main reagents used in the following examples and comparative examples are shown in Table 2.

[0049] Table 2 Names and manufacturers of main experimental reagents

[0050]

[0051] The adhesive performance test was carried out according to the following method:

[0052] 1. Adhesive appearance test: Test the appearance of component A, component B and various adhesive products respectively to observe their transparency, color, liquid fluidity, the presence of crystal flocs and bubbles.

[0053] 2. Adhesive viscosity determination: Use a digital viscometer (SNB-2 model), select the appropriate rotor model according to the viscosity of the adhesive, adjust the speed, and measure the viscosity of all samples.

[0054] 3. Adhesive 180° peel strength test: Apply the adhesive evenly on paper / aluminum foil, paper / paper, paper / PE film, and aluminum foil / PE film, place in a 60°C electric constant temperature air drying oven (DGG-9070B model) for aging for 48 hours, and then use a computer servo tensile material testing machine (HD-B617-S) to perform 180° peel strength test.

[0055] 4. Infrared spectrum test of adhesive: First, scan the potassium bromide crystals with a Fourier transform spectrometer (SHIMADZU IRPresting-21) to make a blank background spectrum. Then, dissolve component A, component B, and the adhesive product with tetrahydrofuran (THF), respectively. Take 2 to 3 drops of the solution and drop them into the potassium bromide crystals. Use an electric hot air blower (HP8110) to evaporate and remove the tetrahydrofuran (THF). Then scan all the samples to obtain infrared spectra.

[0056] Example 1

[0057] A method for preparing a solvent-free polyurethane modified acrylate adhesive comprises the following steps:

[0058] S1. Preparation of component A: Take 39.8 parts of polyether diol (PPG400), add it to a four-necked round-bottom flask, and heat it to 95°C in a water bath; take 20 parts of methyl methacrylate, 30 parts of butyl acrylate, 10 parts of hydroxyethyl acrylate, and 0.1 parts of azobisisobutyronitrile, mix them and add them to a beaker, stir to dissolve, and gradually and slowly add them to the four-necked round-bottom flask with a separatory funnel, stir mechanically, keep the speed at 250r / min, keep the addition within 2 hours, and keep it warm for 0.5 hours, continue to add the remaining 0.1 parts of azobisisobutyronitrile to the volumetric flask at one time, react at 95°C for 1 hour, and make the remaining acrylate mixed monomer react thoroughly. After the reaction is completed, cool to room temperature, test the appearance and viscosity of polyacrylate; seal and store.

[0059] like Figure 1 As shown, the prepared component A is a slightly yellowish transparent viscous liquid. The liquid has good tilting performance at room temperature, and no crystal flocs or bubbles are generated.

[0060] like Figure 2As shown in the figure, the viscosity of component A decreases with the increase of temperature. When the temperature is 55 ℃, an inflection point appears, the viscosity does not change significantly, and the internal friction between molecules tends to be balanced.

[0061] S2, preparation of component B: 41.1 parts of polyether diol (PPG1000) and 58.8 parts of isophorone diisocyanate (IPDI) were added to a four-necked round-bottom flask, mechanically stirred and the speed was maintained at 300 r / min, slowly heated to 50°C, then stopped heating, allowed to self-exotherm to 70-75°C, maintained at 75°C, reacted for 2 hours, added 0.1 parts of butyl tin dilaurate (DBTDL) to the reaction device, and continued to react for 2 hours. After the reaction was completed, it was cooled to room temperature, and the appearance and viscosity of the polyurethane were tested; it was sealed and stored.

[0062] like Figure 3 As shown, component B is a transparent, colorless, viscous liquid. The liquid has good tilting properties at room temperature, and no crystal flocs or bubbles are generated.

[0063] S3. When in use, component A is mixed with component B in volume ratios of 85%, 70%, 55%, 40% and 25% respectively to obtain five groups of adhesives.

[0064] Figure 4 This is a product photo of the adhesive obtained by compounding component A with component B at a volume ratio of 40%.

[0065] The infrared spectrum of component A, component B and the adhesive obtained by mixing component A with component B at a volume ratio of 40% in this embodiment was measured. The results are as follows: Figure 5 As shown. Figure 5 It can be seen that component A is at 3450 cm -1 The peak at 3335 cm is the stretching vibration absorption peak of the hydrogen-bonded -OH group in the hydroxy acrylic acid monomer. -1 The absorption peak at 2260cm is the stretching vibration peak of the NH group in the polyurethane. The two peaks appear simultaneously in the adhesive, indicating that there are two components, A and B, in the compound adhesive molecule. -1 The absorption peak of 1736 cm-1 is attributed to the stretching vibration of -NCO in polyurethane. This peak also exists in the adhesive but its intensity is weakened. It can be inferred that the -NCO group of component B in the adhesive reacts with component A. -1 The absorption peak at 1100 cm is the stretching vibration absorption peak of -C=O in acrylate, indicating the presence of acrylate groups; -1The absorption peaks near the 2960 and 2870 peaks in component A, component B and adhesive exist in all components A, component B and adhesive, which may be caused by the strong absorption of CO in ester, and may also indicate the existence and generation of ester in adhesive; the absorption peaks at 1460 and 1373 are caused by the antisymmetric and symmetric deformation vibration of -CH3. Through infrared spectroscopy analysis, it can be seen that acrylate prepolymer and polyurethane PU prepolymer exist in adhesive, and the -OH group of acrylate in adhesive reacts with the -NCO group of polyurethane, and the acrylate segment and polyurethane segment form crosslinks.

[0066] Embodiment 2:

[0067] A method for preparing a solvent-free polyurethane modified acrylate adhesive comprises the following steps:

[0068] S1. Preparation of component A: Take 39.7 parts of polyether diol (PPG400), add it to a four-necked round-bottom flask, and heat it to 95°C in a water bath; take 18 parts of methyl methacrylate, 31 parts of butyl acrylate, 11 parts of hydroxyethyl acrylate, and 0.15 parts of azobisisobutyronitrile, mix them and add them to a beaker, stir to dissolve, and gradually and slowly add them to the four-necked round-bottom flask with a separatory funnel, stir mechanically, keep the speed at 300 r / min, keep the addition within 2 hours, and keep it warm for 0.5 hours, continue to add the remaining 0.15 parts of azobisisobutyronitrile to the volumetric flask at one time, react at 95°C for 1 hour, and make the remaining acrylate mixed monomer react thoroughly. After the reaction is completed, cool to room temperature, test the appearance and viscosity of polyacrylate; seal and store.

[0069] S2. Preparation of component B: Take 40 parts of polyether diol (PPG1000) and 59.8 parts of isophorone diisocyanate (IPDI), add them to a four-necked round-bottom flask, stir mechanically and keep the speed at 300 r / min, slowly heat to 50°C, then stop heating, let it self-exotherm to 70~75°C, keep the temperature at 75°C, react for 2 hours, add 0.2 parts of butyl tin dilaurate (DBTDL) to the reaction device, and continue to react for 2 hours. After the reaction is completed, cool it to room temperature, test the appearance and viscosity of the polyurethane; seal and store.

[0070] S3. When in use, component A is mixed with component B in volume ratios of 85%, 70%, 55%, 40% and 25% respectively to obtain five groups of adhesives.

[0071] Embodiment 3:

[0072] A method for preparing a solvent-free polyurethane modified acrylate adhesive comprises the following steps:

[0073] S1. Preparation of component A: Take 39.9 parts of polyether diol (PPG400), add it to a four-necked round-bottom flask, and heat it to 95°C in a water bath; take 22 parts of methyl methacrylate, 29 parts of butyl acrylate, 9 parts of hydroxyethyl acrylate, and 0.05 parts of azobisisobutyronitrile, mix them and add them to a beaker, stir to dissolve, and gradually and slowly add them to the four-necked round-bottom flask with a separatory funnel, stir mechanically, keep the speed at 250r / min, keep the addition within 2 hours, and keep it warm for 0.5 hours, continue to add the remaining 0.05 parts of azobisisobutyronitrile to the volumetric flask at one time, react at 90°C for 1 hour, and make the remaining acrylate mixed monomer react thoroughly. After the reaction is completed, cool to room temperature, test the appearance and viscosity of polyacrylate; seal and store.

[0074] S2, preparation of component B: 41.1 parts of polyether diol (PPG1000) and 58.8 parts of isophorone diisocyanate (IPDI) were added to a four-necked round-bottom flask, mechanically stirred and the speed was maintained at 300 r / min, slowly heated to 50°C, then stopped heating, allowed to self-exotherm to 70-75°C, maintained at 75°C, reacted for 2 hours, added 0.1 parts of 0.5 mL of butyl tin dilaurate (DBTDL) to the reaction device, and continued to react for 2 hours. After the reaction was completed, it was cooled to room temperature, and the appearance and viscosity of the polyurethane were tested; it was sealed and stored.

[0075] S3. When in use, component A is mixed with component B in volume ratios of 85%, 70%, 55%, 40% and 25% respectively to obtain five groups of adhesives.

[0076] Comparative Example 1:

[0077] A method for preparing a solvent-free polyurethane modified acrylate adhesive comprises the following steps:

[0078] S1. Preparation of component A: Take 39.8 parts of polyether diol (PPG400), add it to a four-necked round-bottom flask, and heat it to 95°C in a water bath; take 35.13 parts of methyl methacrylate, 49.14 parts of butyl acrylate, 15.73 parts of hydroxyethyl acrylate, and 0.1 parts of azobisisobutyronitrile, mix them and add them to a beaker, stir to dissolve, and gradually and slowly add them dropwise to the four-necked round-bottom flask with a separatory funnel, stir mechanically, keep the speed at 250r / min, keep the addition within 2 hours, and keep it warm for 0.5 hours, continue to add the remaining 0.1 parts of azobisisobutyronitrile at once, react at 95°C for 1 hour, and make the remaining acrylate mixed monomer react thoroughly. After the reaction is completed, cool to room temperature, test the viscosity of the acrylate, and seal and store.

[0079] S2. Preparation of component B: 41.1 parts of polyether diol (PPG1000) and 58.8 parts of isophorone diisocyanate (IPDI) were added to a four-necked round-bottom flask; mechanical stirring was maintained at a speed of 300 r / min, and the mixture was slowly heated to 50°C, and then the heating was stopped, and the mixture was allowed to self-exotherm to 70-75°C, and the temperature was maintained at 75°C, and the reaction was continued for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, and the appearance and viscosity of the polyurethane were tested; the mixture was sealed and stored.

[0080] like Figure 6 As shown, component B is a clear, transparent, colorless, viscous liquid. At room temperature, the liquid has good tilting properties, and no crystal flocs or bubbles are generated.

[0081] S3. When in use, component A is mixed with component B in volume ratios of 85%, 70%, 55%, 40% and 25% respectively to obtain five groups of adhesives.

[0082] Figure 7 This is a product photo of the adhesive obtained by compounding component A with component B at a volume ratio of 40%.

[0083] Comparative Example 2:

[0084] A method for preparing a solvent-free polyurethane modified acrylate adhesive comprises the following steps:

[0085] S1. Preparation of component A: Take 39.8 parts of polyether diol (PPG400), add it to a four-necked round-bottom flask, and heat it to 95°C in a water bath; take 35.13 parts of methyl methacrylate, 49.14 parts of butyl acrylate, 15.73 parts of hydroxyethyl acrylate and 0.1 parts of azobisisobutyronitrile, mix them and add them to a beaker, stir to dissolve, and gradually add them dropwise to the four-necked round-bottom flask with a separatory funnel, stir mechanically, keep the speed at 250r / min, keep the addition within 2 hours, and keep it warm for 0.5 hours, continue to add 0.1 parts of azobisisobutyronitrile at a time, react at 95°C for 1 hour, and make the remaining acrylate mixed monomer react thoroughly. After the reaction is completed, cool to room temperature, test the viscosity of the acrylate, and seal it for storage.

[0086] S2. Preparation of component B: 41.1 parts of polyether diol (PPG3000) and 58.8 parts of isophorone diisocyanate (IPDI) were added to a four-necked round-bottom flask, mechanically stirred and kept at a speed of 300 r / min, slowly heated to 50°C, then stopped heating, allowed to self-exotherm to 70-75°C, maintained at 75°C, and reacted for 4 hours. After the reaction was completed, it was cooled to room temperature, and the appearance and viscosity of the polyurethane were tested; it was sealed and stored.

[0087] like Figure 8 As shown, component B is a clear, transparent, colorless, viscous liquid.

[0088] S3. When in use, component A is mixed with component B in volume ratios of 85%, 70%, 55%, 40% and 25% respectively to obtain five groups of adhesives.

[0089] Fig. 9 This is a product photo of an adhesive obtained by mixing component A with component B at a volume ratio of 40%.

[0090] Depend on Figure 4 , Figure 7 and Fig. 9 From the comparison, it can be seen that there is no obvious difference in the appearance of the three groups of adhesive products. The product appearance is turbid, slightly transparent, viscous liquid. The liquid tilting performance is general at room temperature, and no crystal flocs or bubbles are generated.

[0091] Comparison of adhesive performance test results:

[0092] 1. Temperature-viscosity curve comparison

[0093] Fig.10 The temperature-viscosity curves of component B prepared in comparative example 1, embodiment 1 and comparative example 2 are shown in FIG. Fig.10 It can be seen that compared with Comparative Example 1, under the same temperature conditions, the viscosity of Example 1 is increased by multiples. This is because Example 1 uses butyl tin dilaurate as a catalyst to promote the reaction, thereby improving the viscosity and peel strength. By comparing Comparative Example 1 and Comparative Example 2, it can be seen that under the same temperature conditions, the higher the molecular weight of the polyether diol, the higher the viscosity of component B.

[0094] Figures 11 to 13 The temperature-viscosity curves of the adhesives prepared in Comparative Example 1, Example 1 and Comparative Example 2 are shown respectively. Figure 11~Figure 13 It can be seen that, for each group of adhesives prepared in Comparative Example 1, Example 1 and Comparative Example 2, under the same temperature conditions, the greater the volume percentage of component A, the greater the viscosity. The viscosity depends on the internal friction between molecules. The internal friction of the liquid depends on the attraction between molecules. When the temperature rises, the distance between molecules increases, resulting in a decrease in the attraction between molecules. When the temperature reaches a certain level, the attraction between molecules tends to balance, the internal friction tends to balance, and the final viscosity does not change significantly. By comparison Figures 11 to 13It can be seen that under the same volume percentage of component A, as the temperature increases, the viscosity decreases; the comparative example 1 has an inflection point at 65°C, at which temperature, the viscosity does not change significantly, and the internal friction between molecules tends to be balanced, the embodiment 1 has an inflection point at 60°C, at which temperature, the viscosity does not change significantly, and the internal friction between molecules tends to be balanced, and the comparative example 2 has an inflection point at 60°C, at which temperature, the viscosity does not change significantly, and the internal friction between molecules tends to be balanced. Under the same volume ratio, the viscosity of the adhesive prepared by the embodiment 1 is the largest, the comparative example 2 is the second, and the comparative example 1 has the smallest viscosity.

[0095] 2. Adhesive peel strength comparison

[0096] Fig.14 The following is a comparison chart of the peel strength of each group of adhesives on paper / aluminum foil of Comparative Example 1, Example 1 and Comparative Example 2. Fig.15 The following is a comparison chart of the peel strength of each group of adhesives on paper / paper of Comparative Example 1, Example 1 and Comparative Example 2. Fig.16 The following is a comparison chart of the peel strength of each group of adhesives on paper / PE film of Comparative Example 1, Example 1 and Comparative Example 2. Fig.17 It is a comparison chart of the peel strength of each group of adhesives of Comparative Example 1, Example 1 and Comparative Example 2 on aluminum foil / PE film.

[0097] Depend on Figures 14 to 17 It can be seen that the adhesive with the highest peel strength on paper / aluminum foil and paper / paper is the adhesive with a composition of 40% component A and 60% component B in Example 1, and the peel strengths are 2.971 N / 15mm and 3.567 N / 15mm, respectively; the adhesive with the highest peel strength on paper / PE film and aluminum foil / PE is the adhesive with a composition of 70% component A and 30% component B in Comparative Example 2, and the peel strengths are 1.068 N / 15mm and 0.803 N / 15mm, respectively.

[0098] From the above analysis, it can be seen that the overall comprehensive adhesion degree of Example 1 is the best. The adhesives obtained by compounding Comparative Examples 1 and 2 have poor adhesion properties to some substrates, while the adhesive properties of Example 1 are stronger.

[0099] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. Application of a solvent-free polyurethane modified acrylate adhesive on paper / aluminum foil and paper / paper substrates, characterized in that: The adhesive is composed of component A and component B which are stored independently of each other; wherein, Component A is composed of the following components in parts by mass: 38-42 parts of polyether diol, 18-22 parts of methyl methacrylate, 28-32 parts of butyl acrylate, 8-12 parts of hydroxyethyl acrylate, and 0.1-0.5 parts of azobisisobutyronitrile; the molecular weight of the polyether diol in component A is 300-800; Component B is composed of the following components in parts by mass: 39-43 parts of polyether diol, 58-62 parts of isophorone diisocyanate, and 0.1-0.5 parts of dibutyltin dilaurate; the molecular weight of the polyether diol in component B is 1000; When the adhesive is used, component A and component B are compounded and reacted according to a volume ratio of component A: component B = 40%: 60%; The adhesive is prepared according to the following steps: S1. Preparation of component A: Take polyether diol and heat it to 80-100° C. in a water bath; Take methyl methacrylate, butyl acrylate and hydroxyethyl acrylate and mix them, add part of azobisisobutyronitrile, stir and dissolve, and obtain a mixed solution of acrylate monomer containing azobisisobutyronitrile; slowly drop the mixed solution into the polyether diol and stir, keep the mixture warm for 0.5-1h after the dropwise addition is completed, then add the remaining azobisisobutyronitrile, react at 80-100° C. for 1-2h, cool to room temperature after the reaction is completed, and seal and store; S2, preparation of component B: add isophorone diisocyanate to polyether diol, stir and slowly heat to 40-60°C, stop heating, allow to self-exotherm to 70-80°C, maintain this temperature and continue to react for 2-3h, add 0.1-0.5 parts of dibutyltin dilaurate and continue to react for 2-3h, cool to room temperature after the reaction is completed, and seal and store; S3. When in use, component A and component B are compounded and reacted in a volume ratio of component A: component B = 40%: 60% to obtain the adhesive.

2. A method for preparing the solvent-free polyurethane modified acrylate adhesive according to claim 1, characterized in that: The following steps are involved: S1. Preparation of component A: Take polyether diol and heat it to 80-100° C. in a water bath; Take methyl methacrylate, butyl acrylate and hydroxyethyl acrylate and mix them, add part of azobisisobutyronitrile, stir and dissolve, and obtain a mixed solution of acrylate monomer containing azobisisobutyronitrile; slowly drop the mixed solution into the polyether diol and stir, keep the mixture warm for 0.5-1h after the dropwise addition is completed, then add the remaining azobisisobutyronitrile, react at 80-100° C. for 1-2h, cool to room temperature after the reaction is completed, and seal and store; S2, preparation of component B: add isophorone diisocyanate to polyether diol, stir and slowly heat to 40-60°C, stop heating, allow to self-exotherm to 70-80°C, maintain this temperature and continue to react for 2-3h, add 0.1-0.5 parts of dibutyltin dilaurate and continue to react for 2-3h, cool to room temperature after the reaction is completed, and seal and store; S3. When in use, component A and component B are compounded and reacted in a volume ratio of component A: component B = 40%: 60% to obtain the adhesive.

3. The method for preparing the solvent-free polyurethane modified acrylate adhesive according to claim 2, characterized in that: The stirring speed when azobisisobutyronitrile is added dropwise in step S1 is 200-300 r / min.

4. The method for preparing the solvent-free polyurethane modified acrylate adhesive according to claim 2, characterized in that: The stirring speed in step S2 is 250-350 r / min.

Citation Information

Patent Citations

  • One hundred percent solids acrylic adhesives

    WO1993005099A1